Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/02701960.2013.858332
|View full text |Cite
|
Sign up to set email alerts
|

Hospital to Home: A Geriatric Educational Program on Effective Discharge Planning

Abstract: There has been increased attention on the needs of the burgeoning older adult population, with focus on the limited education and training experiences available in geriatric care. Older adults transitioning between levels of care often require increased attention, and the American Geriatrics Society (AGS) Task Force on the Future of Geriatric Medicine has encouraged greater training opportunities be provided to better understand the needs of this population. The Hospital to Home Program is one model of geriatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…67 The next most common combinations were passive approaches combined with either group learning (9 studies, 15%) 22,27,40,42,45,49,50,58,82 or with practi c al co n s tr u c ti ve ap p r o ach e s (8 s t u d ie s , 13%). 25,26,35,56,66,70,72,81 Use of curriculum was explicitly reported in 37 studies (59%). Four studies included a system approach: one utilized point-of-care, 68 2 had faculty development, 24,52 and 1 had both.…”
Section: Prisma Flowchartmentioning
confidence: 99%
“…67 The next most common combinations were passive approaches combined with either group learning (9 studies, 15%) 22,27,40,42,45,49,50,58,82 or with practi c al co n s tr u c ti ve ap p r o ach e s (8 s t u d ie s , 13%). 25,26,35,56,66,70,72,81 Use of curriculum was explicitly reported in 37 studies (59%). Four studies included a system approach: one utilized point-of-care, 68 2 had faculty development, 24,52 and 1 had both.…”
Section: Prisma Flowchartmentioning
confidence: 99%
“…Według European Heath Committee tylko 16% problemów, z jakimi osoby starsze zgłaszają się do lekarza, dotyczy spraw medycznych, pozostałe to problemy psychologiczne [7]. Stąd też starsze osoby często wymagają większej uwagi, właśnie dlatego The American Geriatrics Society Task Force on the Future of Geriatric Medicine promuje ogromne znaczenie kształcenia się personelu medycznego w celu lepszego zrozumienia oczekiwań tej części populacji [8].…”
Section: Wstępunclassified
“…[7][8][9][10][11] Residents are responsible for care transitions, yet feel they lack the knowledge of how to safely complete these tasks, and studies have found a need to increase resident knowledge in transitions of care. [12][13][14][15][16][17][18][19] Experiential learning theory suggests that learning is best done in the context in which it occurs, and that interactions are fundamental to gain understanding. 20,21 To address the need for experiential learning, we embedded an innovative curriculum in our existing postgraduate year 1 (PGY-1) ambulatory block.…”
Section: Introductionmentioning
confidence: 99%